Prevalence and molecular characterization of Pentatrichomonas hominis in Siberian tigers (Panthera tigris altaica) in northeast China. Issue 4 (18th February 2022) - ZHANG, Hongbo; ZHANG, Nan; GONG, Pengtao; CHENG, Shuqin; WANG, Xiaocen; LI, Xin; HOU, Zhijun; LIU, Chang; BI, Tianqi; WANG, Bobo; CHENG, Yidan; LI, Jianhua; et al.
Abstract : The overall infection rate of Pentatrichomonas hominis in Siberian tigers in northeast China is 31.3%. All the P. hominis identified in Siberian tigers belonged to genotype CC1.